Characteristics of Healthy Cornflakes (Study of the Proportion of Pre-Cooked White Corn Flour : Pre-Cooked Red Bean Flour and the Proportion of tapioca) - Lihan Candra Asi, Sri Alam Syah; Rosida, Rosida; Wicaksono, Luqman Agung (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Flakes are a convenient type of food that can be developed to meet the body's nutritional needs. Cornflakes, which have a high starch content, can be combined with protein and fat from red beans and snakehead fish, as well as tapioca as a source of amylopectin that affects the texture of cornflakes. The purpose of this research is to determine the effect of the proportion of white corn flour to red bean flour and the proportion of tapioca. The Randomized Block Design (RBD) method was used with Factor I being the proportion of white corn flour to red bean flour (80:20, 75:25, and 70:30), and Factor II being different proportions of tapioca (5%, 10%, and 15%). The observational data were analyzed using ANOVA and followed by Duncan's test. The best treatment determination was carried out using the De Garmo method. The best cornflakes were obtained with a proportion of 70% pre-cooked white corn flour, 30% pre-cooked red bean flour, and 10% tapioca, resulting in a moisture content of 3.13%, ash content of 2.88%, protein content of 8.26%, carbohydrate content of 80.88%, fat content of 4.90%, starch content of 33.11%, rehydration capacity of 46.54%, and breaking strength of 15.25 N.